Military Practices and Experiences and their Effects on the Environment - Adow, Anass Hamadelneel (Journal of Ecohumanism, 2024)
International humanitarian law provides the guidelines to meet environmental standards during military operations. Thus, we explore the effect of military spending on CO2 emissions in Saudi Arabia by using data from 1971-2022 and the cointegration technique. Moreover, the effect of fossil fuels on CO2 emissions is also tested along with testing the Environmental Kuznets Curve (EKC) in the model. The EKC is corroborated by the effect of economic progress on CO2 emissions in the long and short runs. Moreover, military spending raises CO2 emissions. A 1% increasing military spending raises 0.0414% of CO2 emissions. Thus, military operations and activities are responsible for environmental problems. The effect of fossil fuels is also positive and a 1% increasing fossil fuels raises 1.0984% of CO2 emissions. The short-run results substantiate the long-run conclusions with different elasticity parameters. The study suggests reducing military spending and operations to protect the environment. Moreover, fossil fuel consumption should also be reduced by shifting energy needs toward clean sources.